Unprecedented quality factors at accelerating gradients up to 45 MVm−1 in niobium superconducting resonators via low temperature nitrogen infusion. (8th August 2017) - Grassellino, A; Romanenko, A; Trenikhina, Y; Checchin, M; Martinello, M; Melnychuk, O S; Chandrasekaran, S; Sergatskov, D A; Posen, S; Crawford, A C; Aderhold, S; Bice, D
Abstract: We report the finding of new surface treatments that permits one to manipulate the niobium resonator nitrogen content in the first few nanometers in a controlled way, and the resonator fundamental Mattis–Bardeen surface resistance and residual resistance accordingly. In particular, we find surface 'infusion' conditions that systematically (a) increase the quality factor of these 1.3 GHz superconducting radio frequency (SRF) bulk niobium resonators, up to very high gradients; (b) increase the achievable accelerating gradient of the cavity compared to its own baseline with state-of-the-art surface processing. Cavities subject to the new surface process have more than two times the state-of-the-art Q at 2 K for accelerating fields >35 MVm −1 . Moreover, very high accelerating gradients ∼45 MVm −1 are repeatedly reached, which correspond to peak magnetic surface fields of 190 mT, among the highest measured for bulk niobium cavities. These findings open the opportunity to tailor the surface impurity content distribution to maximize performance in Q and gradients, and have therefore very important implications on future performance and cost of SRF based accelerators. They also help deepen the understanding of the physics of the RF niobium cavity surface.